Development of virtual reality on material: Archimedes’ Law (VIRMA) to improve student learning outcomes - Dhanty Novya Bunga Prillyanti; Mita Anggaryani (Jurnal Inovasi Teknologi Pendidikan, 2023)
The development of this Virtual Reality (VR) with an artificial environment consisting of scenes and 3D objects is expected to be a problem solution from a low conceptual understanding of Archimedes' Law material. This study aims to make physics learning media with Virtual Reality on Archimedes' Law (VIRMA) material. The purpose of his research is to describe the validity of making Virtual Reality learning media on material: Archimedes' Law (VIRMA), to tell the effectiveness of making Virtual Reality learning media on material: Archimedes' Law (VIRMA) based on learning outcomes and student response questionnaires. The type of research used in this research is development research according to the ADDIE model with one group pre-test post-test research design. The result showed that the development of Virtual Reality media in Archimedes' Law (VIRMA) material is very valid, with a percentage value of 85.9%. Using Virtual Reality media on material: Archimedes' Law can provide hands-on learning experiences, facilitate a deeper understanding of abstract concepts, and improve student learning outcomes with n-gain in the medium category 0,67. In addition, the response questionnaire showed that 93.7% of students agreed that Virtual Reality media was enjoyable and effective in helping to understand Archimedes' Law. Using the Virtual Reality media on the material is recommended: Archimedes' Law, which can increase student involvement, stimulate student interest in learning physics, and improve student learning outcomes.